Two-year course of non-suicidal self-injury in an adolescent clinical cohort: the role of childhood adversity in interaction with cortisol secretion - Reichl, Corinna; Schär, Selina; Lerch, Stefan; Hedinger, Nicole; Brunner, Romuald; Koenig, Julian; Kaess, Michael (Psychoneuroendocrinology, 2024)
Aim - Non-suicidal self-injury (NSSI) is a highly prevalent phenomenon during adolescence. Nonetheless, research on predictors of the clinical course of NSSI over time is still scarce. The present study aimed at investigating the impact of adverse childhood experiences (ACE) and hypothalamus-pituitary-adrenal (HPA) axis functioning on the longitudinal course of NSSI. - Methods - In a sample of n = 51 help-seeking adolescents engaging in NSSI, diurnal cortisol secretion (CAR, cortisol awakening response; DSL, diurnal slope), hair cortisol concentrations and ACE were assessed at baseline. Clinical outcome was defined by change in the frequency of NSSI in the past 6 months measured 12 and 24 months after the baseline assessments. Mixed-effects linear regression models were used to test for effects of ACE and HPA axis functioning on the course of NSSI. - Results - ACE and HPA axis functioning did not show main but interaction effects in the prediction of NSSI frequency over time: Adolescents with a low severity of ACE and either an increased CAR or a flattened DSL showed a steep decline of NSSI frequency in the first year followed by a subsequent increase of NSSI frequency in the second year. - Conclusions - Our findings could be interpreted in the sense of high diurnal cortisol concentrations in the absence of ACE being favorable for clinical improvement on the short-term but bearing a risk of allostatic load and subsequent increase of NSSI frequency. In contrast, adolescents with severe ACE may benefit from elevated cortisol concentrations leading to slower but lasting decreases of NSSI frequency.
Online verfügbar 6 June 2024, Version des Artikels 17 June 2024
Gesehen am 10.01.2025